2012
DOI: 10.1186/1476-069x-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to arsenic may reduce human semen quality: associations derived from a Chinese cross-sectional study

Abstract: BackgroundRecent observations in in vitro and in vivo models suggest that arsenic (As) is an endocrine disruptor at environmentally-relevant levels. When exposed to As, male rats and mice show steroidogenic dysfunction that can lead to infertility. However, the possible effects of As on human male semen quality remain obscure.MethodsWe monitored the profile of As species in the urine of a reproductive-age human cohort and assessed its association with semen quality. Men (n = 96) were recruited in an infertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 53 publications
(57 reference statements)
1
42
1
Order By: Relevance
“…The association continued to exist in separate examinations of smokers and nonsmokers. Cd levels in seminal plasma were compared with the levels in nonsmokers from a general population group as reported by other studies (Keck et al 1995) and were lower than those in infertile smokers (Xu et al, 2012; Telisman et al, 2007). Our research finding added evidence that low exposure to Cd in the general population could link to decreased sperm quality, particularly in viability.…”
Section: Discussionmentioning
confidence: 84%
“…The association continued to exist in separate examinations of smokers and nonsmokers. Cd levels in seminal plasma were compared with the levels in nonsmokers from a general population group as reported by other studies (Keck et al 1995) and were lower than those in infertile smokers (Xu et al, 2012; Telisman et al, 2007). Our research finding added evidence that low exposure to Cd in the general population could link to decreased sperm quality, particularly in viability.…”
Section: Discussionmentioning
confidence: 84%
“…Though maternal exposures are likely to be of greater importance, evidence from studies conducted in populations with and without assisted reproduction suggests the relevance of paternal factors for placental function, and possibly for preterm delivery (Sartorius and Nieschlag, 2010). While associations have been reported for environmental iAs exposure and semen quality in animals (Li et al, 2012) and men (Xu et al, 2012), data to specifically address DNA adducts and fragmentation in association with iAs exposure among men has not yet been published to the best of our knowledge. Given the couple-based nature of human reproduction investigation into potential effects for male exposure is warranted.…”
Section: Recommendationsmentioning
confidence: 99%
“…Human epidemiological studies have illustrated the possible association between declining male sperm quality and exposure of men to environmental pollutants [17,18,121,122]. Earlier studies revealed that nearly all the components of the male reproductive tract are potential targets of EDCs.…”
Section: Discussionmentioning
confidence: 99%